High-purity spinel particles and method for producing same
By producing spinel particles through controlled mixing and firing of high purity magnesium and aluminum compounds, the particles achieve both thermal conductivity and dielectric properties, enhancing their performance in resin compositions for high-frequency communication devices.
Patent Information
- Application Number
- JP2024531694
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-07-28
- Filing Date
- 2023-07-20
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-07-20
AI Technical Summary
Existing spinel particles do not adequately address both thermal conductivity and dielectric properties, and their production methods do not ensure spherical shapes for improved filling properties in resin mixtures.
The production of spinel particles involves mixing and firing high purity magnesium and aluminum compounds with controlled impurity levels and particle sizes, resulting in spherical or true spherical particles with excellent thermal conductivity and low dielectric properties.
The resulting spinel particles exhibit high thermal conductivity and low dielectric properties, enabling improved filling properties and reduced power consumption in resin compositions, suitable for high-frequency communication devices.
Smart Images

Figure 0007608683000003 
Figure 0007608683000004 
Figure 0007608683000005
Abstract
Description
[Technical field]
[0001] The present invention relates to high purity spinel particles and a method for producing the same. [Background technology]
[0002] The spinel particles are MgAl 2 O 4 Represented by the general formula AB 2 X 4 In addition to being used as jewelry, due to its porous structure and ease of modification, it is used in applications such as electrode protective films, fluorescent emitters, catalyst carriers, adsorbents, photocatalysts, and heat-resistant insulating materials. In particular, due to its excellent thermal conductivity, research is being conducted on its use as a heat dissipating filler (Patent Documents 1 and 2).
[0003] Meanwhile, in recent years, the speed and capacity of information communication has rapidly increased, and millimeter-wave electromagnetic wave communication infrastructure, such as the fifth generation communication system (5G) and even the sixth generation mobile communication system (6G), is attracting attention. As a result, there is a demand for heat dissipation fillers with excellent dielectric properties (low dielectric constant, low dielectric loss tangent) to reduce transmission loss in printed circuit boards for power high-frequency devices.
[0004] In response to this, Patent Document 1 discloses spinel particles that contain magnesium atoms, aluminum atoms, oxygen atoms, and molybdenum, and have a crystallite diameter of 220 nm or more in the
[0111] plane. It is described that the obtained particles have a significantly large crystallite diameter in the
[0111] plane, and as a result, have excellent thermal conductivity.
[0005] In addition, Patent Document 2 describes MgAl obtained by firing a raw material containing at least an alumina-based compound and a magnesium or zinc compound as main components. 2 O 4 or ZnAl 2 O 4Specifically, the paper focuses on chemical resistance and describes a thermally conductive complex oxide whose absolute value of the rate of change in mass in chemical resistance tests against hydrochloric acid, sulfuric acid, nitric acid, and sodium hydroxide is 2% or less. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2017 / 221372 [Patent Document 2] JP 2016-135841 A Summary of the Invention [Problem to be solved by the invention]
[0007] All of these documents focused on thermal conductivity or thermal conductivity and chemical resistance, and did not consider dielectric properties. In addition, the inventors believe that in order to obtain low dielectric properties in a molded product, it is important to make the spinel particles spherical and improve the filling properties when mixed with a resin, but there is still room for further study on the method of producing spherical spinel particles.
[0008] The present invention has been made in view of the above circumstances, and provides high-purity spinel particles that combine high thermal conductivity and low dielectric properties, and a method for producing the same. [Means for solving the problem]
[0009] As a result of intensive research conducted by the inventors in order to achieve the above object, it was discovered that spinel particles obtained by firing fine particles of a high-purity magnesium-based compound and an aluminum-based compound have high purity and excellent thermal conductivity and dielectric properties, and this led to the completion of the present invention.
[0010] That is, the present invention includes the following aspects. (1) Spinel particles containing at least magnesium atoms, aluminum atoms, and oxygen atoms, Spinel particles, wherein the amount of atoms other than the above atoms is less than 0.27 atomic %. (2) Spinel particles containing at least magnesium atoms, aluminum atoms, and oxygen atoms, Spinel particles, the number of calcium atoms being less than 0.02 atomic % relative to the sum of the numbers of magnesium atoms and aluminum atoms. (3) Spinel particles according to (1) or (2) above, having an average particle size of 75 μm or less. (4) The dielectric tangent at 1 GHz is 1.0×10 -3 The spinel particles according to any one of the above (1) to (3), wherein the average particle diameter is less than 100 nm. (5) A resin composition comprising the spinel particles according to any one of (1) to (4) above and a resin. (6) A molded product of the resin composition described in (5) above. (7) A method for producing spinel particles, comprising mixing an aluminum-based compound and a magnesium-based compound and firing the mixture, comprising the steps of: The magnesium-based compound is a fine particle having an average particle size of less than 4 μm, The method for producing spinel particles, wherein the magnesium-based compound contains impurities in an amount of less than 1.0 atomic %. (8) A method for producing spinel particles, comprising mixing an aluminum-based compound and a magnesium-based compound and firing the mixture, comprising the steps of: The magnesium-based compound is a fine particle having an average particle size of less than 4 μm, The method for producing spinel particles, wherein the amount of calcium atoms contained in the magnesium-based compound is 0.6 atomic % or less. (9) The method according to (7) or (8) above, wherein the aluminum-based compound has a spherical or true spherical shape. Effect of the Invention
[0011] The present invention provides spinel particles of higher purity than conventional spinel particles, and is excellent in both thermal conductivity and dielectric properties. In addition, the spinel particles of the present invention can be easily obtained by mixing and firing a fine, high-purity magnesium compound and an aluminum compound, and therefore the spinel particles of the present invention are highly productive and have excellent practicality. [Brief description of the drawings]
[0012] [Figure 1] 1 is an SEM image of the spinel particles of Example 1. [Diagram 2] 1 is an SEM image of spinel particles of Example 3. [Diagram 3] 1 is an SEM image of spinel particles of Example 4. [Figure 4] 1 is an SEM image of spinel particles of Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, an embodiment of the present invention will be described in detail. <Spinel particles> One embodiment of the spinel particle of the present invention is characterized in that the spinel particle contains at least magnesium atoms, aluminum atoms, and oxygen atoms, and the amount of atoms other than the above-mentioned atoms is less than 0.27 atomic % relative to the number of atoms in the spinel particle.
[0014] One embodiment of the spinel particle of the present invention is a spinel particle containing at least magnesium atoms, aluminum atoms, and oxygen atoms, and is characterized in that the number of calcium atoms is less than 0.02 atomic % relative to the sum of the numbers of magnesium atoms and aluminum atoms.
[0015] The spinel particles are spinel particles containing at least magnesium atoms, aluminum atoms, and oxygen atoms, and the amount of other atoms is less than 0.27 atomic %, more preferably less than 0.2 atomic %, and particularly preferably less than 0.1 atomic %. If the amount is less than the upper limit, the resulting spinel particles have excellent dielectric properties, which is preferable.
[0016] The spinel particles are spinel particles containing at least magnesium atoms, aluminum atoms, and oxygen atoms, and the number of calcium atoms relative to the sum of the numbers of magnesium atoms and aluminum atoms is less than 0.02 atomic %, more preferably less than 0.01 atomic %, and particularly preferably less than 0.005 atomic %. If it is less than the upper limit, the resulting spinel particles have excellent dielectric properties, which is preferable.
[0017] The average particle size of the spinel particles is preferably 75 μm or less, more preferably 35 μm or less, and particularly preferably 10 μm or less, which is preferable because when the spinel particles are mixed with a resin and processed into a sheet or the like, the surface of the processed product does not become uneven.
[0018] In this specification, the "average particle size" of spinel particles refers to a value measured using a particle size distribution system using laser diffraction scattering, such as a laser diffraction scattering particle size distribution measuring device MT3300EXII (manufactured by Microtrack Bell Co., Ltd.), and is expressed as D50.
[0019] The aforementioned average particle diameter may be the arithmetic average value of the longest diameter (longest diameter: the longest distance when each particle is sandwiched between two parallel line segments in the observation field or on the image) determined from the particle image of the primary particles of the spinel particles in a two-dimensional image taken with a scanning electron microscope (SEM), and the obtained value is almost the same as the measured value obtained by the above method. The spinel particles to be measured are at least 50 spinel particles randomly selected from those whose outlines are entirely identifiable.
[0020] The dielectric constant of the spinel particles is preferably equal to or less than 20, more preferably equal to or less than 15, and particularly preferably equal to or less than 10. If it is within the above range, it is preferable because power consumption, i.e., heat generation and noise can be suppressed when the particles are made into a resin composition.
[0021] The dielectric loss tangent of the spinel particles at 1 GHz is 1.0×10 -3 It is preferable that the value is less than 8.0×10 -4 More preferably, it is 5.0×10 or less. -4 It is particularly preferable that the content is within the above range, since when the resin composition is prepared, power consumption, i.e., heat generation and noise can be suppressed.
[0022] Examples of the shape of the spinel particles include polyhedron, sphere, true sphere, ellipse, cylinder, polygonal column, needle, rod, plate, disk, flake, scale, etc. Among these, a spherical shape is preferred because it enhances the packing property when mixed with a resin, and a true sphere is particularly preferred because it further reduces the viscosity of the mixture, improves the packing rate, and is more likely to form a close-packed structure.
[0023] When the composition contains spinel particles having a spherical shape, it is preferable that 50% or more of the particles, based on mass or number, have a spherical shape, more preferably 80% or more of the particles have a spherical shape, and even more preferably 90% or more of the particles have a spherical shape.
[0024] In addition, when the shape is spherical or true spherical, the particles are packed closely together during molding of the resin composition to easily avoid contact and fixation with other particles. In addition, the shape reduces the fractal dimension of the particle outline, suppressing the void ratio when packed. As a result, the closest packed structure provides excellent thermal conductivity and dielectric properties.
[0025] In this specification, the shape is judged visually from a scanning electron microscope (SEM) image, but it can also be judged by calculating the circularity. For example, the circularity may be 0.7 or more, may be 0.75 or more, or may be 0.8 or more. The above-mentioned "circularity" can be calculated from "4 x π x area / circumference^2", and the area and circumference can each be obtained by observation with a scanning electron microscope (SEM).
[0026] The crystal structure of the spinel particles is MgAl 2 O 4 The spinel particles of the present embodiment described below are mainly composed of a spinel type crystal structure, but may contain an impurity phase to the extent that it does not adversely affect the dielectric loss tangent.
[0027] <Content of each atom> (Magnesium atom) The content of magnesium atoms in the spinel particles is not particularly limited, but the structural formula of the spinel particles is preferably Mg x Al y O z In this specification, the content of magnesium atoms in the spinel particles is a value measured by X-ray fluorescence elemental analysis (XRF).
[0028] (aluminum atom) The content of aluminum atoms in the spinel particles is not particularly limited, but the structural formula of the spinel particles is preferably Mg x Al y O z When expressed as above, y is preferably in the range of 1.8 to 2.2, and more preferably in the range of 1.9 to 2.1. In this specification, the content of aluminum atoms in the spinel particles is a value measured by X-ray fluorescence elemental analysis (XRF).
[0029] (oxygen atom) The content of oxygen atoms in the spinel particles is not particularly limited, but the structural formula of the spinel particles is preferably Mg x Al y O z In this case, z is preferably in the range of (x+y+1.2) to (x+y+0.8), and more preferably in the range of (x+y+1.1) to (x+y+0.9).
[0030] (Other atoms) The other atoms refer to impurities that are present in the raw materials or that are inevitably mixed into the spinel particles during the manufacturing process, and are essentially unnecessary elements that affect the properties of the spinel particles.
[0031] The other atoms in the spinel particles are not particularly limited, but include silicon, iron, potassium, sodium, calcium, etc. These impurities may be contained alone or in combination, but the content is preferably less than 0.27 atomic % relative to the atoms in the spinel particles. If the content is within the above range, it is assumed that scattering of phonons (lattice vibrations) due to the impurities is suppressed, and thus the dielectric properties of the spinel particles are excellent. The content of other atoms in the spinel is measured by X-ray fluorescence elemental analysis (XRF).
[0032] In the spinel particles, the number of calcium atoms as impurities is preferably less than 0.02 atomic % relative to the sum of the numbers of magnesium and aluminum atoms.Within this range, it is presumed that scattering of phonons (lattice vibrations) due to impurities caused by calcium atoms substituted for magnesium atoms is suppressed, and the spinel particles have an excellent dielectric tangent.The content of calcium atoms in the spinel particles is a value measured by X-ray fluorescence elemental analysis (XRF).
[0033] In the spinel particles of the present invention, it is sufficient that either the content of impurities (silicon, iron, potassium, sodium, calcium, etc.) or the number of calcium atoms relative to the sum of the numbers of magnesium and aluminum atoms falls within the above-mentioned range, or both of them may be satisfied. It is particularly preferable that both fall within the above-mentioned range, since spinel particles having better dielectric properties can be obtained.
[0034] <Method of manufacturing spinel particles> The method for producing spinel particles includes a step of firing a mixture containing a magnesium-based compound and an aluminum-based compound.
[0035] [Mixing process] The mixing step is a step of mixing a magnesium-based compound and an aluminum-based compound to obtain a mixture. In this case, the mixed state of the magnesium-based compound and the aluminum-based compound is not particularly limited. When mixing the two, simple mixing is performed by putting the raw materials in a bag or the like and shaking the bag to mix the powder, mechanical mixing using a grinder or mixer, mixing using a mortar, etc. In this case, the obtained mixture may be in either a dry state or a wet state, but it is preferable that it is in a dry state from the viewpoint of cost.
[0036] In the mixing step, the mixing ratio of the magnesium-based compound and the aluminum-based compound is not particularly limited, but they are preferably mixed so that the molar ratio of the magnesium element of the magnesium-based compound to the aluminum element of the aluminum-based compound (aluminum element / magnesium element) is 1.8 or more and 2.2 or less, and more preferably 1.9 or more and 2.1 or less. The contents of the mixture will be explained below.
[0037] (Magnesium compounds) Examples of magnesium compounds include, but are not limited to, metallic magnesium, magnesium derivatives, magnesium oxoacid salts, magnesium organic salts, and hydrates thereof. Examples of magnesium derivatives include magnesium oxide, magnesium hydroxide, magnesium peroxide, magnesium fluoride, magnesium chloride, magnesium bromide, magnesium iodide, magnesium hydride, magnesium diboride, magnesium nitride, magnesium sulfide, and the like. Examples of magnesium oxoacid salts include magnesium carbonate, calcium magnesium carbonate, magnesium nitrate, magnesium sulfate, magnesium sulfite, magnesium perchlorate, trimagnesium phosphate, magnesium permanganate, magnesium phosphate, and the like. Examples of magnesium organic salts include magnesium acetate, magnesium citrate, magnesium malate, magnesium glutamate, magnesium benzoate, magnesium stearate, magnesium acrylate, magnesium methacrylate, magnesium gluconate, magnesium naphthenate, magnesium salicylate, magnesium lactate, magnesium monoperoxyphthalate, and the like. These magnesium compounds may be used alone or in combination of two or more.
[0038] Among these, magnesium oxide, magnesium hydroxide, magnesium carbonate, magnesium acetate, magnesium nitrate, or magnesium sulfate is preferred, and magnesium oxide, magnesium hydroxide, magnesium nitrate, or magnesium acetate is more preferred.
[0039] The volume-based average particle diameter D50 of the magnesium-based compound measured by laser diffraction particle size distribution measurement can be made smaller without aggregation, so that homogenization during firing can be achieved and spinel particles with a more uniform particle size can be obtained. The average particle diameter D50 is 0.01 μm or more and less than 4 μm, more preferably 0.1 μm or more and less than 2 μm, even more preferably 0.5 μm or more and less than 2 μm, and particularly preferably 0.5 μm or more and less than 1.5 μm. If it is equal to or more than the lower limit, it is possible to suppress the aggregation of particles during mixing. If it is less than the upper limit, it is possible for magnesium atoms to diffuse and enter into the aluminum-based compound particles without destroying the shape of the aluminum-based compound, and for particles with a uniform shape to grow.
[0040] The magnesium compound may be a commercially available product or may be prepared by oneself. When preparing the magnesium compound by oneself, the reactivity for producing spinel particles can be adjusted. For example, magnesium hydroxide having a small particle size can be obtained by neutralizing an acidic aqueous solution of magnesium ions with a base. The magnesium hydroxide having a small particle size obtained is highly reactive, so the crystallite size of the spinel particles obtained by using it tends to be large.
[0041] Commercially available or prepared magnesium compounds may contain impurities such as silicon, iron, potassium, sodium, calcium, phosphorus, sulfur, chlorine, etc. The total amount of these impurities, when measured by X-ray fluorescence elemental analysis (XRF) and converted to the number of atoms, is preferably less than 1.0 atomic % relative to magnesium, more preferably 0.5 atomic % or less, and even more preferably 0.3 atomic % or less.
[0042] The amount of calcium atoms contained in commercially available or prepared magnesium compounds is preferably 0.6 atomic % or less, more preferably 0.4 atomic % or less, and even more preferably 0.3 atomic % or less.
[0043] (Aluminum compounds) The aluminum-based compound is not particularly limited, but may include aluminum derivatives such as metal aluminum, alumina (aluminum oxide), aluminum hydroxide, aluminum sulfide, aluminum nitride, aluminum fluoride, aluminum chloride, aluminum bromide, and aluminum iodide; aluminum oxoacid salts such as aluminum sulfate, sodium aluminum sulfate, potassium aluminum sulfate, ammonium aluminum sulfate, aluminum nitrate, aluminum perchlorate, aluminum aluminate, aluminum silicate, and aluminum phosphate; aluminum organic salts such as aluminum acetate, aluminum lactate, aluminum laurate, aluminum stearate, and aluminum oxalate; alkoxy aluminum such as aluminum propoxide and aluminum butoxide; aluminum-magnesium-containing compounds such as magnesium aluminate, hydrotalcite, and magnesium aluminum isopropoxide; and hydrates thereof. Among these, it is preferable to use aluminum oxide, aluminum hydroxide, aluminum chloride, aluminum sulfate, aluminum nitrate, and hydrates thereof, and it is more preferable to use aluminum oxide and aluminum hydroxide. The above aluminum compounds may be used alone or in combination of two or more kinds.
[0044] The volume-based average particle diameter D50 of the aluminum-based compound measured by laser diffraction particle size distribution measurement is preferably smaller than that of the aluminum-based compound in the range where no aggregation occurs, because the reactivity during firing is improved and spinel particles with no impurity phase and high purity can be obtained. The particle diameter of the aluminum raw material correlates with the particle diameter of the resulting spinel particles, so it is appropriately selected according to the particle diameter of the desired spinel particles. The average particle diameter D50 of the aluminum-based compound is 0.01 μm or more and 70 μm or less, preferably 0.1 μm or more and 30 μm or less, more preferably 0.1 μm or more and 15 μm or less, and most preferably 0.5 μm or more and 10 μm or less.
[0045] In order to obtain the above-mentioned average particle diameter D50, the aluminum-based compound as the raw material may be pulverized using a pulverizer, etc. From the viewpoint of the particle shape of the aluminum-based compound described below and the shape of the obtained spinel particles, it is more preferable to use, as the raw material, an aluminum-based compound that does not require pulverization for particle size adjustment.
[0046] The shape of the aluminum compound may be any of polyhedral, spherical, true spherical, elliptical, cylindrical, polygonal columnar, needle-like, rod-like, plate-like, disk-like, thin plate-like, and scaly, but from the viewpoint of the shape of the obtained spinel particles, it is more preferable that it is spherical or true spherical. According to the manufacturing method of this embodiment, magnesium atoms diffuse and enter into the aluminum compound particles, so that the raw material aluminum compound can grow without losing its shape during particle growth, and the shape of the obtained spinel particles can be easily controlled.
[0047] The crystal structure of the aluminum-based compound is not particularly limited and may be a single phase or a mixed phase. When the crystal structure is a mixed phase, the shape of the aluminum-based compound is often spherical.
[0048] [Firing process] The mixture is fired at high temperature in a firing furnace to obtain spinel particles.
[0049] The firing temperature is not particularly limited as long as the desired spinel particles can be obtained, but is preferably 1100 to 1600° C., more preferably 1200 to 1500° C., and particularly preferably 1300 to 1400° C. A firing temperature of 1100° C. or higher is preferable because unreacted raw materials are suppressed, while a firing temperature of 1600° C. or lower is preferable in terms of suitability for mass production because a general-purpose firing furnace can be used.
[0050] The firing time is not particularly limited, but is preferably 1 to 20 hours, and more preferably 5 to 10 hours. A firing time of 1 hour or more is preferable because highly crystalline spinel particles can be obtained. On the other hand, a firing time of 20 hours or less is preferable because the production cost can be reduced.
[0051] The firing atmosphere may be an air atmosphere, an inert gas atmosphere such as nitrogen gas or argon gas, an oxygen atmosphere, an ammonia gas atmosphere, or a carbon dioxide atmosphere, although an air atmosphere is preferred from the viewpoint of production costs.
[0052] The pressure during firing is not particularly limited, and firing may be performed under normal pressure, elevated pressure, or reduced pressure. From the viewpoint of production costs, firing is preferably performed under normal pressure.
[0053] The heating means is not particularly limited, but it is preferable to use a calcination furnace. Examples of calcination furnaces that can be used in this case include a box furnace, a tunnel furnace, a roller hearth furnace, a rotary kiln, and a muffle furnace.
[0054] In comparison with typical production methods such as a flame method, it is believed that in the above-mentioned production method, magnesium atoms do not undergo surface diffusion or grain boundary diffusion during particle growth, but rather undergo volume diffusion with the diffusion path being within the aluminum-based compound particles, and as a result, it is assumed that it has become possible for the particles to grow while maintaining the shape of the raw material aluminum-based compound. Furthermore, the production method of the present invention is a production method with excellent productivity since it does not require pretreatment such as adsorbing magnesium atoms onto the surface of the aluminum-based compound.
[0055] [Cooling process] The cooling step is a step in which the spinel particles that have grown into crystals in the firing step are cooled and crystallized into particles.
[0056] The cooling rate is not particularly limited, but is preferably 1 to 1000°C / hour, more preferably 5 to 500°C / hour, and even more preferably 100 to 500°C / hour. A cooling rate of 1°C / hour or more is preferable because the manufacturing time can be shortened. On the other hand, a cooling rate of 1000°C / hour or less is preferable because the firing container is less likely to crack due to heat shock and can be used for a long time. The cooling method is not particularly limited, and may be natural cooling or a cooling device may be used.
[0057] The manufacturing method of the present invention may include a post-treatment step. The post-treatment step is a step of removing additives and the like. The post-treatment step may be performed after the above-mentioned firing step, after the above-mentioned cooling step, or after the firing step and the cooling step. Moreover, the post-treatment step may be repeated two or more times as necessary.
[0058] Post-treatment methods include washing and high temperature treatment, which may be performed in combination. The washing method is not particularly limited, but for example, the metal oxide can be removed by washing with water, an aqueous ammonia solution, an aqueous sodium hydroxide solution, an acidic aqueous solution, or the like. As a method of high temperature treatment, a method of raising the temperature to the sublimation point or boiling point of the additive or higher can be mentioned.
[0059] [Crushing process] The spinel particles obtained by firing may aggregate and not satisfy the particle size range suitable for the present invention, in which case they may be crushed as necessary to satisfy the particle size range suitable for the present invention.
[0060] The pulverizing method is not particularly limited, and any conventionally known pulverizing method such as a ball mill, a jaw crusher, a jet mill, a disk mill, a spectromill, a grinder, or a mixer mill can be used.
[0061] [Classification process] The spinel particles can be classified to adjust the average particle size, improve the powder flowability, or suppress the increase in viscosity when mixed with a binder to form a matrix. "Classification" refers to the operation of classifying particles into groups based on their size.
[0062] The classification method may be either wet or dry, but from the viewpoint of productivity, dry classification is preferred. Dry classification includes classification by sieving, as well as wind classification, which classifies based on the difference between centrifugal force and fluid drag, but from the viewpoint of classification accuracy, wind classification is preferred, and can be performed using a classifier such as an air classifier utilizing the Coanda effect, a swirling air classifier, a forced vortex centrifugal classifier, or a semi-free vortex centrifugal classifier.
[0063] The above-mentioned pulverization step and classification step can be carried out at any stage required, including before or after the organic compound layer forming step described later. Depending on whether or not the pulverization or classification is carried out and the selection of the conditions therefor, for example, the average particle size of the obtained particles can be adjusted.
[0064] <Resin composition> According to one aspect of the present invention, there is provided a composition comprising spinel particles and a resin, which may further comprise a curing agent, a curing catalyst, a viscosity modifier, a plasticizer, etc., as necessary.
[0065] (Spinel particles) As the spinel particles, those explained in the "spinel particles" above can be used, and therefore the explanation thereof will be omitted here.
[0066] The spinel particles may be surface-treated by the method described below, which can further improve the thermal conductivity of the spinel particles. For example, surface-treated spinel particles can be produced by attaching a surface treatment layer containing an organic compound to at least a portion of the surface of the spinel particles obtained as described above.
[0067] By having a surface treatment layer attached to at least a portion of the surface of untreated spinel particles, wettability with the resin contained in the resin composition is improved, and adhesion to the spinel particles is improved, which suppresses the generation of voids that tend to form on the surface of the spinel particles and reduces loss in thermal conductivity, thereby improving the thermal conductivity of molded products of the resin composition, for example. Such technical effects are achieved by having a surface treatment layer based on an organic compound or a cured product thereof attached to a portion of the surface of the spinel particles, and cannot be achieved, for example, when the surface treatment agent is removed from the spinel particles by baking after the surface treatment.
[0068] When a plurality of types of spinel particles are used, at least one of the plurality of types may be a spinel particle having a surface treatment layer.
[0069] Specifically, the untreated spinel particles are mixed with a surface treatment agent capable of forming a surface treatment layer containing an organic compound, and the surface treatment agent is adhered to at least a portion of the surface of the untreated spinel particles, followed by, for example, drying or curing, to produce surface-treated spinel particles.
[0070] When the surface treatment agent itself is an organic compound that is not reactive but has adsorptive properties, or when the surface treatment agent is in the form of a solution or dispersion in which it is dissolved or dispersed in a liquid medium, drying may be performed for the purpose of promoting adsorption or removing the liquid medium, and when the surface treatment agent is an organic compound that has reactivity, the above-mentioned surface treatment layer can be formed by curing based on the reactive groups of the compound. Note that when the surface treatment agent is attached to the entire surface of the untreated spinel particles, the untreated spinel particles will be covered with a surface treatment layer.
[0071] The surface treatment agent is preferably a non-polar silane compound. Since the non-polar silane compound does not have a polar substituent, deterioration of the dielectric properties can be suppressed. The polar substituent refers to a group capable of hydrogen bonding or an ionic dissociation group. Such a polar substituent is not particularly limited, but examples thereof include -OH, -COOH, -COOM, -NH 3 , -NR 4 + A - , -CONH 2 Here, M is a cation such as an alkali metal, an alkaline earth metal, or a quaternary ammonium salt, R is H or a hydrocarbon group having 8 or less carbon atoms, and A is an anion such as a halogen atom.
[0072] The treatment method using the surface treatment agent may be a known and commonly used method, for example, a spray method using a fluid nozzle, a dry method using stirring with shear force, a ball mill, a mixer, etc., or a wet method using an aqueous or organic solvent, etc. Surface treatment using a shear force is desirably carried out to a degree that does not cause damage to the filler.
[0073] The temperature in the system in the dry method or the temperature for drying or curing after the treatment in the wet method is appropriately determined within a range in which the surface treatment agent does not undergo thermal decomposition depending on the type of the surface treatment agent. For example, it is preferable to heat the surface treatment agent at a temperature of 80 to 230°C.
[0074] The amount of the non-volatile content or cured product of the surface treatment agent in the surface treatment layer relative to the untreated spinel particles is not particularly limited, but from the viewpoint of improving functions such as thermal conductivity, it is preferable that the amount of the non-volatile content or cured product of the surface treatment agent be 0.01 to 10 parts per 100 parts by mass of the untreated spinel particles.
[0075] Whether or not an unknown spinel particle corresponds to the surface-treated spinel particle of the present invention can be confirmed, for example, by observing whether a chemical structure corresponding to the surface treatment agent itself or its cured product, or the presence of silicon atoms, titanium atoms, or phosphorus atoms can be observed in an extract obtained by immersing or boiling the unknown spinel particle in a solvent that dissolves the non-volatile component of the surface treatment agent or the cured product, or in the spinel particle surface itself, by infrared absorption analysis (IR) or atomic absorption spectrometry (AAS).
[0076] (resin) The resin is not particularly limited, and examples thereof include thermoplastic resins and thermosetting resins.
[0077] The thermoplastic resin is not particularly limited, and known and commonly used resins used for molding materials and the like can be used. Specific examples include polyethylene resins, polypropylene resins, polymethyl methacrylate resins, polyvinyl acetate resins, ethylene-propylene copolymers, ethylene-vinyl acetate copolymers, polyvinyl chloride resins, polystyrene resins, polyacrylonitrile resins, and polyamide resins. Examples of the thermoplastic resin include polycarbonate resins, polyacetal resins, polyethylene terephthalate resins, polyphenylene oxide resins, polyphenylene sulfide resins, polysulfone resins, polyethersulfone resins, polyetheretherketone resins, polyarylsulfone resins, thermoplastic polyimide resins, thermoplastic urethane resins, polyaminobismaleimide resins, polyamideimide resins, polyetherimide resins, bismaleimide triazine resins, polymethylpentene resins, fluorinated resins, liquid crystal polymers, olefin-vinyl alcohol copolymers, ionomer resins, polyarylate resins, acrylonitrile-ethylene-styrene copolymers, acrylonitrile-butadiene-styrene copolymers, and acrylonitrile-styrene copolymers.
[0078] The thermosetting resin is a resin that has the property of being substantially insoluble and infusible when cured by heating or radiation, a catalyst, or the like, and generally, a known and commonly used resin used for molding materials, etc. can be used. Specific examples include phenolic resins, epoxy resins, urea resins, resins having a triazine ring, (meth)acrylic resins, vinyl resins, unsaturated polyester resins, bismaleimide resins, polyurethane resins, diallyl phthalate resins, silicone resins, resins having a benzoxazine ring, cyanate ester resins, and the like. Examples of phenolic resins include novolac-type phenolic resins and resol-type phenolic resins. Examples of novolac-type phenolic resins include phenol novolac resins and cresol novolac resins. Examples of resol-type phenolic resins include unmodified resol phenolic resins and oil-modified resol phenolic resins. Examples of oils used for oil modification include tung oil, linseed oil, walnut oil, and the like. Examples of epoxy resins include bisphenol type epoxy resins, aliphatic chain modified bisphenol type epoxy resins, novolac type epoxy resins, biphenyl type epoxy resins, polyalkylene glycol type epoxy resins, etc. Examples of bisphenol type epoxy resins include bisphenol A epoxy resins, bisphenol F epoxy resins, etc. Examples of novolac type epoxy resins include novolac epoxy resins, cresol novolac epoxy resins, etc. Examples of resins having a triazine ring include melamine resins, etc. Examples of vinyl resins include vinyl ester resins, etc.
[0079] The above-mentioned resins may be used alone or in combination of two or more kinds. In this case, two or more kinds of thermoplastic resins may be used, two or more kinds of thermosetting resins may be used, or one or more kinds of thermoplastic resins and one or more kinds of thermosetting resins may be used.
[0080] (hardening agent) The curing agent is not particularly limited, and any known curing agent can be used. Specific examples of the curing agent include amine compounds, amide compounds, acid anhydride compounds, and phenol compounds.
[0081] Examples of the amine compounds include diaminodiphenylmethane, diethylenetriamine, triethylenetetramine, diaminodiphenylsulfone, isophoronediamine, imidazole, and BF 3- Examples of the compound include amine complexes and guanidine derivatives.
[0082] Examples of the amide-based compound include dicyandiamide, and polyamide resins synthesized from a dimer of linoleic acid and ethylenediamine.
[0083] Examples of the acid anhydride compounds include phthalic anhydride, trimellitic anhydride, pyromellitic anhydride, maleic anhydride, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylnadic anhydride, hexahydrophthalic anhydride, and methylhexahydrophthalic anhydride.
[0084] Examples of the phenol-based compound include phenol novolac resin, cresol novolac resin, aromatic hydrocarbon formaldehyde resin modified phenol resin, dicyclopentadiene phenol addition type resin, phenol aralkyl resin (Zylok resin), polyhydric phenol novolac resin synthesized from a polyhydric hydroxy compound such as resorcin novolac resin and formaldehyde, naphthol aralkyl resin, trimethylol methane resin, tetraphenylol ethane resin, naphthol novolac resin, naphthol-phenol co-condensed novolac resin, naphthol Examples of the polyphenol compounds include polyphenol compounds such as aryl-cresol co-condensed novolak resin, biphenyl-modified phenol resin (a polyphenol compound in which a phenol nucleus is linked by a bismethylene group), biphenyl-modified naphthol resin (a polyphenol compound in which a phenol nucleus is linked by a bismethylene group), aminotriazine-modified phenol ... melamine, benzoguanamine, or the like), and alkoxy group-containing aromatic ring-modified novolak resin (a polyphenol compound in which a phenol nucleus and an alkoxy group-containing aromatic ring are linked by formaldehyde).
[0085] The above-mentioned curing agents may be used alone or in combination of two or more kinds.
[0086] (Cure accelerator) The curing accelerator has a function of accelerating the curing when the resin composition is cured. The curing accelerator is not particularly limited, but examples thereof include phosphorus-based compounds, tertiary amines, imidazole, organic acid metal salts, Lewis acids, and amine complex salts. The above-mentioned curing accelerators may be used alone or in combination of two or more kinds.
[0087] The curing catalyst functions to promote the curing reaction of a compound having a polymerizable functional group in place of the curing agent. The curing catalyst is not particularly limited, and a known and commonly used thermal polymerization initiator or active energy ray polymerization initiator can be used. The curing catalyst may be used alone or in combination of two or more kinds.
[0088] (Viscosity modifier) The viscosity modifier has the function of adjusting the viscosity of the resin composition. The viscosity modifier is not particularly limited, and for example, organic polymers, polymer particles, inorganic particles, etc. can be used. The above-mentioned viscosity modifiers may be used alone or in combination of two or more kinds.
[0089] (Plasticizer) The plasticizer has the function of improving the processability, flexibility, and weather resistance of the thermoplastic synthetic resin. The plasticizer is not particularly limited, and examples of the plasticizer that can be used include phthalates, adipates, phosphates, trimellitates, polyesters, polyolefins, and polysiloxanes. The above-mentioned plasticizers may be used alone or in combination of two or more kinds.
[0090] [mixture] The resin composition of the present invention can be obtained by mixing the spinel particles, the resin, and, if necessary, other ingredients. There is no particular limitation on the mixing method, and the mixture can be mixed by a known, commonly used method. When the resin is a thermosetting resin, a general method of mixing the thermosetting resin with spinel particles, etc., is to thoroughly mix a predetermined amount of the thermosetting resin, spinel particles, and other components as necessary with a mixer, etc., and then knead with a three-roll mill, etc., to obtain a liquid composition having fluidity. In another embodiment, a method of mixing the thermosetting resin with spinel particles, etc., is to thoroughly mix a predetermined amount of the thermosetting resin, spinel particles, and other components as necessary with a mixer, etc., and then melt-knead with a mixing roll, extruder, etc., and then cool to obtain a solid composition. Regarding the mixed state, when a curing agent, catalyst, etc. are blended, it is sufficient that the curing resin and the blend are thoroughly and uniformly mixed, but it is more preferable that the spinel particles are also uniformly dispersed and mixed.
[0091] The content of the spinel particles is preferably 5% by volume or more and 95% by volume or less, more preferably 20% by volume or more and 90% by volume or less, and particularly preferably 30% by volume or more and 80% by volume or less, based on the volume of the resin composition. When the content of the spinel particles is equal to or more than the lower limit, the resin composition can be provided with better thermal conductivity and dielectric properties. On the other hand, when the content of the spinel particles is equal to or less than the upper limit, the resin composition has excellent flowability and can be easily molded.
[0092] When the resin is a thermoplastic resin, a typical method for mixing the thermoplastic resin with spinel particles and the like includes a method in which the thermoplastic resin, the spinel particles, and, if necessary, other components are mixed in advance using various mixers such as a tumbler or a Henschel mixer, and then melt-kneaded using a mixer such as a Banbury mixer, a roll, a Brabender, a single-screw kneading extruder, a twin-screw kneading extruder, a kneader, a mixing roll, etc. The temperature for melt-kneading is not particularly limited, but is usually in the range of 100°C or higher and 320°C or lower. A coupling agent may be added externally to the resin composition, since this can further increase the fluidity of the resin composition and the filling ability of the filler such as the spinel particles. By adding a coupling agent externally, the adhesion between the resin and the spinel particles can be further increased, the interfacial thermal resistance between the resin and the spinel particles can be reduced, and the thermal conductivity of the resin composition can be improved.
[0093] The coupling agent includes an organic silane compound.
[0094] Examples of the organic silane compound include alkyltrimethoxysilanes having an alkyl group with 1 to 22 carbon atoms, such as methyltrimethoxysilane, dimethyldimethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, isopropyltrimethoxysilane, isopropyltriethoxysilane, pentyltrimethoxysilane, hexyltrimethoxysilane, and octenyltrimethoxysilane; alkyltrichlorosilanes having an alkyl group with 1 to 22 carbon atoms, such as 3,3,3-trifluoropropyltrimethoxysilane; tridecafluoro-1,1,2,2-tetrahydrooctyl)trichlorosilane; phenyltrimethoxysilane, phenyltriethoxysilane, p-chloromethylphenyltrimethoxysilane, p-chloromethylphenyltriethoxysilane; γ-glycidoxypropyltrimethoxysilane; Epoxy silanes such as glycidoxypropyltriethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and glycidoxyoctyltrimethoxysilane; amino silanes such as γ-aminopropyltriethoxysilane, N-β(aminoethyl)γ-aminopropyltrimethoxysilane, N-β(aminoethyl)γ-aminopropylmethyldimethoxysilane, γ-aminopropyltrimethoxysilane, and γ-ureidopropyltriethoxysilane; mercapto silanes such as 3-mercaptopropyltrimethoxysilane; vinyl silanes such as p-styryltrimethoxysilane, vinyltrichlorosilane, vinyltris(β-methoxyethoxy)silane, vinyltrimethoxysilane, vinyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, and methacryloxyoctyltrimethoxysilane; and further examples of polymeric epoxy, amino, and vinyl silanes. The organic silane compound may be contained alone or in combination of two or more kinds.
[0095] The amount of the coupling agent added is not particularly limited, but is preferably from 0.01% by mass to 5% by mass, and more preferably from 0.1% by mass to 3% by mass, based on the mass of the resin.
[0096] <Application> According to one embodiment of the present invention, the resin composition of the present invention is used for a low dielectric heat dissipation material. Generally, aluminum oxide is often used as a thermally conductive material from the viewpoint of cost, and other materials such as boron nitride, aluminum nitride, magnesium oxide, and magnesium carbonate have also been used. However, these materials, for example, aluminum oxide does not have sufficient dielectric properties, boron nitride has anisotropy derived from its crystal structure and therefore does not provide uniform dielectric properties in the resin composition, and aluminum nitride, magnesium oxide, and magnesium carbonate have low water resistance and therefore do not have sufficient dielectric properties. Therefore, a material that combines both thermal conductivity and dielectric properties has not been found.
[0097] In contrast, the spinel particles of the present invention have a high purity not found in the past, and therefore have both excellent thermal conductivity and dielectric properties, and a resin composition containing the spinel particles is suitable for use in a low dielectric heat dissipation material. Furthermore, when the shape of the spinel particles of the present invention is spherical or true spherical, anisotropy is reduced and uniform dielectric properties can be obtained in the resin composition, making the spinel particles particularly suitable for use in low dielectric materials.
[0098] Since the resin composition of the present invention has excellent thermal conductivity and dielectric properties, it can be used as a base material or substrate for a single-layer or multilayer printed circuit board, a flexible printed circuit board, etc. It can also be suitably used as an insulating material for wiring, particularly for high-frequency signal wiring, such as a coverlay, a solder resist, a build-up material, an interlayer insulating agent, a bonding sheet, an interlayer adhesive, and a bump sheet for a flip-chip bonder.
[0099] In addition, spinel particles can also be used for applications such as jewelry, catalyst carriers, adsorbents, photocatalysts, optical materials, phosphors, heat-resistant insulating materials, substrates, and sensors.
[0100] According to one embodiment of the present invention, there is provided a molded product obtained by molding the above-mentioned resin composition. Since the spinel particles of the present invention contained in the molded product have excellent thermal conductivity and dielectric properties, the molded product is preferably used as a low dielectric heat dissipation member. This can improve the heat dissipation function of the device, and can contribute not only to making the device smaller and lighter and improving its performance, but also to improving the communication function in high-frequency circuits. EXAMPLES
[0101] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the examples, the numbers are calculated based on the number of atoms unless otherwise specified.
[0102] (Analysis of elemental content in magnesium-based compounds used as raw materials) A composition analysis was performed using approximately 5 g of magnesium-based compounds using a fluorescent X-ray analyzer Supermini200 (manufactured by Rigaku Corporation). Using the results of the XRF analysis, the amount of impurities was calculated from the molar ratio (number of atoms) of elements other than oxygen, i.e., the amount of impurities (atomic %) = (number of atoms other than Mg) / (number of Mg atoms) x 100. Similarly, the amount of Ca impurity (atomic %) was calculated as (number of Ca atoms) / (number of Mg atoms)×100.
[0103] (Synthesis of spinel particles) <Example 1> A mixture was obtained by mixing 70 g of alumina particles (Denka, DAW-05, spherical, average particle size 6.4 μm) and 40 g of magnesium hydroxide (Kisuma 5Q-S, Kyowa Chemical Industry, average particle size 0.66 μm, Ca impurity amount undetected, total impurity amount 0.13 atomic %) in an absolute mill (Osaka Chemical Co., Ltd.). The mixture was placed in a crucible and heated to 1300 °C at 5 °C / min in a ceramic electric furnace, and held at 1300 °C for 10 hours for firing. The temperature was then lowered to room temperature at 5 °C / min, and the crucible was removed to obtain approximately 90 g of white powder.
[0104] <Example 2> The same procedure as in Example 1 was carried out except that the firing temperature was changed to 1400°C.
[0105] <Example 3> The same procedure as in Example 1 was repeated, except that the magnesium hydroxide was changed to Magseeds X-6 (average particle size 0.81 μm, Ca impurity content 0.1 atomic %, total impurity content 0.1 atomic %) manufactured by Konoshima Chemical Co., Ltd.
[0106] <Example 4> The same procedure as in Example 1 was repeated, except that the magnesium hydroxide was changed to MAGSTAR #5 manufactured by Tateho Industries (average particle size: 0.99 μm; Ca impurity content: 0.28 atomic %; total impurity content: 0.7 atomic %).
[0107] <Example 5> The same procedure as in Example 1 was carried out, except that the alumina particles were changed to DAW-03 (spherical, average particle size 4.9 μm) manufactured by Denka.
[0108] <Example 6> The same procedure as in Example 1 was carried out, except that the alumina particles were changed to DAW-01 (spherical, average particle size 1.9 μm) manufactured by Denka.
[0109] <Comparative Example 1> A mixture was obtained by mixing 70 g of alumina particles (Denka, DAW-05, spherical, average particle size 6.4 μm) and 27.67 g of magnesium oxide (Kyowa Chemical Industry, Kyowamag MF-150, average particle size 0.71 μm, Ca impurity content 0.64 atomic %, total impurity content 1.7 atomic %) in an absolute mill (Osaka Chemical Co., Ltd.). The mixture was placed in a crucible and heated to 1300°C at 5°C / min in a ceramic electric furnace, and then held at 1300°C for 10 hours for firing. The temperature was then lowered to room temperature at 5°C / min, and the crucible was removed to obtain approximately 90 g of white powder.
[0110] <Comparative Example 2> The same procedure as in Comparative Example 1 was repeated except that the firing temperature was changed to 1400°C.
[0111] <Comparative Example 3> The same procedure as in Comparative Example 1 was repeated, except that the magnesium hydroxide was changed to MAGSTAR #20 manufactured by Konoshima Chemical Co., Ltd. (average particle size 4 μm, Ca impurity content 0.29 atomic %, total impurity content 0.29 atomic %).
[0112] [Evaluation method] The obtained spinel particles were measured and evaluated according to the following methods.
[0113] (Measurement of dielectric properties) The spinel particles obtained in the examples and comparative examples were used as test pieces and filled into an EM Lab cavity resonator CP-001-PW. The dielectric constant and dielectric loss tangent at 1 GHz were measured using a Keysight network analyzer P9373A.
[0114] (Average particle size) A small amount of the spinel particle powder obtained in the examples and comparative examples was placed in a beaker, 50 mL of 0.5% sodium hexametaphosphate aqueous solution was added, and then the mixture was dispersed for 2 minutes using an ultrasonic homogenizer, Sonifier 450D (manufactured by Branson Co., Ltd.) to prepare a measurement sample. The volume cumulative standard D50 of this measurement sample was measured using a laser diffraction scattering type particle size distribution measuring device, MT3300EXII (manufactured by Microtrack Bell Co., Ltd.).
[0115] (Analysis of the amount of elements contained in spinel particles) A composition analysis was performed on approximately 5 g of the prepared sample using a fluorescent X-ray analyzer Supermini200 (Rigaku Corporation). Using the results of XRF analysis, the amount of impurities was calculated from the molar ratio (number of atoms) of elements other than oxygen. That is, the amount of impurities (atomic %) = (number of atoms other than Al·Mg) / (number of Al atoms + number of Mg atoms) × 100. The ratio of Al to Mg was calculated by the ratio of the number of atoms using the same method. Similarly, the amount of Ca impurity (atomic %) was calculated as follows: (number of Ca atoms) / (number of Al atoms+number of Mg atoms)×100.
[0116] The crystal phase was measured using a Rigaku X-ray diffractometer Ultima IV (40 kV, 40 mA, CuKα radiation). The spinel particles in the examples and comparative examples are MgAl 2 O 4 No other impurity phases were identified.
[0117] The results of each of the above evaluations are shown in Table 1. "ND" stands for "not detected."
[0118] [Table 1]
[0119] From Comparative Example 3, it was found that if a magnesium-based compound with a large particle size is used, the mechanism by which the magnesium source diffuses into the aluminum is disrupted and the particles become amorphous, and therefore it is necessary to use a fine particle magnesium-based compound.
[0120] (Preparation of Resin Composition) <Example 7> 30.7 g of DIC-PPS LR100G (X-1, polyphenylene sulfide resin manufactured by DIC Corporation, density 1.35 g / cm3) as a thermoplastic resin and 69.3 g of the spinel particles obtained in Example 1 were uniformly dry-blended, and then melt-kneaded using a resin melt-kneading device, Lab Plastomill, at a kneading temperature of 300°C and a rotation speed of 80 rpm to obtain a polyphenylene sulfide resin composition with a content of the particles of 40% by volume. The filler content (volume %) in the resin composition was calculated from the density of the thermoplastic resin and the density of the thermally conductive filler.
[0121] (Method for measuring thermal conductivity of thermoplastic resin composition) The obtained resin composition was injection molded using a tabletop injection molding machine (Injection Molding IM 12 manufactured by Xplore) at a cylinder temperature of 320°C and a mold temperature of 140°C to prepare a test piece with a diameter of 10 mm and a thickness of 0.2 mm. The thermal conductivity at 25°C was measured using a thermal conductivity measuring device (LFA467 HyperFlash manufactured by NETZSCH).
[0122] (Examples 8 to 9, Comparative Example 4) A polyphenylene sulfide resin composition having a filler content of 40% by volume was prepared and its thermal conductivity was measured in the same manner as in Example 7. The fillers used are as shown in Table 2. In Comparative Example 4, DAW-05 (spherical alumina, manufactured by Denka Co., Ltd.) was used as the filler.
[0123] [Table 2]
[0124] The resin composition containing the spinel particles of this embodiment has a higher thermal conductivity than a resin composition containing alumina, which generally has high thermal conductivity, and it can be said that spinel particles having both high thermal conductivity and low dielectric tangent have been realized.
Claims
1. Spinel particles containing at least magnesium atoms, aluminum atoms, and oxygen atoms, The average particle size of the spinel particles is 3.2 μm or more and 10 μm or less, the shape of the spinel particles is spherical or true spherical and has a circularity of 0.8 or more; The amount of atoms other than the above atoms is less than 0.27 atomic %, and the dielectric loss tangent at 1 GHz is 1.0 × 10 -3 , spinel particles.
2. Spinel particles containing at least magnesium atoms, aluminum atoms, and oxygen atoms, The average particle size of the spinel particles is 3.2 μm or more and 10 μm or less, the shape of the spinel particles is spherical or true spherical and has a circularity of 0.8 or more; The number of calcium atoms is less than 0.02 atomic % relative to the sum of the numbers of magnesium atoms and aluminum atoms, and the dielectric loss tangent at 1 GHz is 1.0 × 10 -3 , spinel particles.
3. A resin composition comprising the spinel particles according to claim 1 or 2 and a resin.
4. A molded product of the resin composition according to claim 3.
5. A method for producing spinel particles, comprising mixing and firing an aluminum-based compound and a magnesium-based compound, The aluminum-based compound has a spherical or true spherical shape, the magnesium-based compound is a fine particle having an average particle size of 0.5 μm or more and 1.5 μm or less, The method for producing spinel particles, wherein the magnesium-based compound contains impurities in an amount of less than 1.0 atomic %.
6. A method for producing spinel particles, comprising mixing and firing an aluminum-based compound and a magnesium-based compound, The aluminum-based compound has a spherical or true spherical shape, the magnesium-based compound is a fine particle having an average particle size of 0.5 μm or more and 1.5 μm or less, The magnesium compound contains calcium atoms in an amount of 0.6 atomic % or less.
7. The method of claim 5 for obtaining spinel particles according to claim 1.
8. The method of claim 6 for producing spinel particles according to claim 2.
Citation Information
Patent Citations
Preparation method of high-purity spherical magnesium aluminate spinel nano-powder
CN109748303A
JP1971007321Y1
Polycrystalline monolithic magnesium aluminate spinel
JP2014005540A
Spinel powder and method of producing the same
JP2016121049A
Heat-conductive composite oxide, heat-conductive resin composition and coating liquid
JP2016135841A